Evaluación del sistema de gestión bajo los parámetros de las normas iso 9001: 008 y la ley 1441 de 2013, para la compañía IPS Ser Asistencia & Transporte Para Discapacitados S.A.S. (2014)
The objective of this paper is to evaluate the Integrated Management System under the parameters of the ISO 9001: 2008 and the 1441 of 2013 that are currently implemented in the company IPS SER ASSISTANCE AND TRANSPORTATION FOR DISABILITIES SAS, in order to determine the effectiveness and efficiency of the Management System, knowing its current status and the good or bad practices developed in the process of implementation, maintenance and improvement thereof, according to the results obtained, a set of recommendations is generated to be taken into account in order to establish and to develop an Integrated Management System that is functional, adequate and convenient for the company. This work is aimed at giving the necessary guidelines to focus on the effort and interest to implement, maintain and improve an Integrated Management System that guarantees profitability, sustainability and growth of the company.